The Art of Archiving an Uprising (Global Media Journal - German Edition, 2020)
As argued by scholars such as Lina Khatib, Ariella Azoulay and W. J. T. Mitchell, the production and circulation of images recorded by citizens played a crucial role during the 2011 Egyptian uprising. The use of images attracted global attention, mobilized action and actively performed the protests’ crucial aims to renegotiate the country’s body and image politics. The inherent act of protest in citizen photography and the “war of presence” spilled over into the act of archiving the protests as a form of resistance in itself. Consequently, a large number of online archive projects were launched during the 2011 uprising. What role does this large body of visual material and the online archives that store it play today, eight years after the outbreak of the uprising? With a focus on Egypt, this paper asks whether the dynamics of these archives “died” with the violent crackdown on public protest and the increased censorship imposed on citizens by the current military regime. Through an examination of archive “858: An Archive of Resistance” by Mosireen Collective, I propose ways in which digital archives containing images produced by civilians serve as sites on which the “war of presence” can continue to be fought within present-day Egypt.
Keywords: Egyptian uprising; Mosireen; Archiving; Post-revolution; Visuality; Arab uprisings